2012
DOI: 10.1007/s00167-012-2088-1
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted navigation for the intraoperative assessment of lower limb alignment in high tibial osteotomy can avoid outliers compared with the conventional technique

Abstract: Purpose Longterm outcomes after valgization high tibial osteotomy (HTO) to treat varus osteoarthritis seem to depend mainly on correction precision. Intraoperative assessment of leg alignment based on radiological visualization of the mechanical axis is difficult and its precision is limited. A promising approach to improving precision is to make use of navigation systems. The case-control study reported here involved the evaluation of patients whose varus osteoarthritis had been treated by open-wedge high tib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 45 publications
(81 reference statements)
1
77
0
1
Order By: Relevance
“…Our findings agreed with previous studies that reported comparable operation time in both groups [13,15], although they conflicted with some other articles that reported longer operative times in the navigation group [10,12,14]. Furthermore, the additional operation time in navigation group was only about two minutes in our series, which was definitely shorter than previous studies reporting longer operation times ranging from ten to 23 minutes [10,12,14].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Our findings agreed with previous studies that reported comparable operation time in both groups [13,15], although they conflicted with some other articles that reported longer operative times in the navigation group [10,12,14]. Furthermore, the additional operation time in navigation group was only about two minutes in our series, which was definitely shorter than previous studies reporting longer operation times ranging from ten to 23 minutes [10,12,14].…”
Section: Discussionsupporting
confidence: 80%
“…However, both surgeons were highly experienced in high tibial osteotomy before the start of this series, as confirmed by the results of the operative time and the target coronal alignment achievement. The operative time in the each group was far shorter than those of other reports, although we did not include about 15-20 minutes of wound closure time in the operation time [10,13,15]. The proportion of the coronal alignment outliers was less than those mean values of the previous studies in the literature [10,12,[14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a surgical technique involving the creation of a bone wedge in the proximal tibia in order to eliminate the axial deviations suffered in the lower limb. The main purpose of the intervention is to realign the mechanical axis of the lower limb and, consequently, to redistribute the forces in the joint by unloading the affected section [5,6,10,11,16]. The main limitation of the correction is an angular one, not being allowed to exceed 18-20°, for larger values it is necessary to perform total prosthesis.…”
Section: High Tibial Osteotomy (Hto)mentioning
confidence: 99%
“…17 Previous researchers reported that use of image-free navigation systems improved the intraoperative technique. [17][18][19][20][21][22] These systems can be monitored 2-or 3-dimensionally in real time. Meanwhile, a computed tomography (CT)ebased navigation system, which is related to both accurate preoperative planning and accurate intraoperative technique, has already been used to plan the osteotomy plane preoperatively and to insert guide wires on the virtual osteotomy plane on-screen intraoperatively in closedwedge high tibial osteotomy.…”
mentioning
confidence: 99%